Ex situ Conservation of Legumes (Fabaceae) in the Indonesian Botanical Gardens - Aisyah, Siti Vanessa; Putri, Dwi Hilda (Microbiotech, 2024)
The Fabaceae family is widely known for its many useful values ranging from food ingredients, ornamental plants, natural dyes, building materials, to the content of secondary compounds that can be used as medicine. Seeing the many potentials and benefits possessed by the Fabaceae family, proper conservation and management efforts are needed so that there is no big worry about the threat of extinction in the future. Botanical gardens were built to reduce the rate of extinction of plant diversity in their habitat. Botanical gardens are known as ex-situ conservation partners, which means they have a responsibility to preserve, manage and maintain natural and cultural resources. This research aims to determine the types of Fabaceae that have been conserved ex-situ in the Indonesian Botanical Gardens (KRI), determine the conservation status of Fabaceae types that have been collected at KRI, and determine the distribution of collections of Fabaceae types that have been collected at KRI. The results of the study show that of 124 genera consisting of 360 species from the Fabaceae family which have been conserved ex-situ in the National Botanical Gardens (KRI), 63% of the species from the Fabaceae family have been included in the IUCN Redlist category, while the other 37% still do not have them. conservation status and 10 of these species have a wide distribution in ex-situ conservation efforts in KRI.